John Quincy Adams and the Politics of Slavery : Selections from the Diary. - Waldstreicher, David (Oxford University Press, 2016)
Expertly edited by David Waldstreicher and Matthew Mason, John Quincy Adams and the Politics of Slavery offers an unusual perspective on the dramatic and shifting politics of slavery in the early republic, as it moved from the margins to the center of public life and from the shadows to the substance of Adams's politics. The editors provide a lucid introduction to the collection as a whole and frame the individual documents with brief and engaging insights, rendering both Adams's life and the controversies over slavery into a mutually illuminating narrative. By juxtaposing Adams's personal ref.